2007
DOI: 10.1177/0022022107300273
|View full text |Cite
|
Sign up to set email alerts
|

Two Decades of Change in Cultural Values and Economic Development in Eight East Asian and Pacific Island Nations

Abstract: In a 1982 publication, Ng et al. surveyed the cultural values of select East Asian and Pacific Island nations. In 2002, this study repeated their work, using the same sampling frame, questionnaire, and collaborators, where possible. The authors also reclassified the 1982 and 2002 survey results using Schwartz's cultural-level value dimensions. Submission versus Dionysian values that differentiated the nations in 1982 continued to do so in 2002. Furthermore, nations that endorsed Mastery (and rejected Harmony) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 29 publications
2
24
0
1
Order By: Relevance
“…The collectivist nature of the Soviet society, and especially its vertical collectivist structure enforced through Communist authorities (Triandis, 1995), was a key feature that allowed policies aimed at long-term economic growth, despite extreme poverty induced at the time of their implementation (Service, 2009) with perceived increase in wellbeing, rather than states in transition to capitalism (Inglehart & Baker, 2000;Allen, et al, 2007). In Soviet Russia, the economy grew fastest when the living conditions were at their worst, while the slowing down of growth was directly related to increased freedoms, comfort, privacy, and goods made for personal use, which could also explain the decline in published expressions of collectivism during the same period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The collectivist nature of the Soviet society, and especially its vertical collectivist structure enforced through Communist authorities (Triandis, 1995), was a key feature that allowed policies aimed at long-term economic growth, despite extreme poverty induced at the time of their implementation (Service, 2009) with perceived increase in wellbeing, rather than states in transition to capitalism (Inglehart & Baker, 2000;Allen, et al, 2007). In Soviet Russia, the economy grew fastest when the living conditions were at their worst, while the slowing down of growth was directly related to increased freedoms, comfort, privacy, and goods made for personal use, which could also explain the decline in published expressions of collectivism during the same period.…”
Section: Discussionmentioning
confidence: 99%
“…YellenÕs (1990) ethnography of !Kung suggests that wealth correlates with movement away from collectivist living, hoarding instead of gift-giving, and diminishing values of intimacy and interdependence. While cooperation can enhance public wealth, the rapid growth of wealth can result in defection from cooperative norms (Ball 1999) (Yang, 1996;Yang, 1988;Inglehart & Baker, 2000;Allen, et al, 2007). For instance, scholars have noted that economic growth in the United States correlates with a decline in conformity (Alwin, 1989;Bond & Smith, 1996), withdrawal from social groups and institutions (Glenn, 1987;Putnam, 2000), a rise in individualism (Roberts & Helson, 1997;Twenge & Campbell, 2001;Twenge & Campbell, 2008), narcissism , and a decreasing need for social approval (Twenge & Im, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing literature on mapping cultural values associated with developed and developing nations (Allen et al, 2007). Strong economies, for example, are found to be associated with individualism (Hofstede, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they found that countries with higher GNP per capita tend to be more secular. Besides, Allen et al (2007) found that persons from richer countries tended to endorse secular values, such as Dionysianism, Autonomy, and Egalitarianism; whereas poorer countries tended to endorse traditional values, such as Submission, Embeddedness, and Hierarchy. In other words, countries with higher HDI tend to have a more secular societal context of values while countries with lower HDI tend to have a more traditional societal context.…”
Section: The Role Of Human Developmentmentioning
confidence: 96%